Safety of dobutamine or adenosine stress cardiac magnetic resonance imaging in patients with left ventricular thrombus - Weberling, Lukas D.; Seitz, Sebastian; Salatzki, Janek; Ochs, Andreas; Heins, Jannick; Haney, Ailís Ceara; Siry, Deborah; Frey, Norbert; André, Florian; Steen, Henning (Clinical research in cardiology, 2023)
Background: Left ventricular (LV) thrombus formation is a common but potentially serious complication, typically occurring after myocardial infarction. Due to perceived high thromboembolic risk and lack of safety data, stress cardiac magnetic resonance (CMR) imaging especially with dobutamine is usually avoided despite its high diagnostic yield. This study aimed to investigate the characteristics, safety and outcome of patients with LV thrombus undergoing dobutamine or vasodilator stress CMR. Methods: Patients undergoing stress CMR with concomitant LV thrombus were retrospectively included. Risk factors, comorbidities, and previous embolic events were recorded. Periprocedural safety was assessed for up to 48 h following the examination. Major adverse cardiac events (MACE) 12 months before the diagnosis were compared to 12 months after the exam and between patients and a matched control group. Additionally, patients were followed up for all-cause mortality. Results: 95 patients (78 male, 65 ± 10.7 years) were included. Among them, 43 patients underwent dobutamine (36 high-dose, 7 low-dose) and 52 vasodilator stress CMR. Periprocedural safety was excellent with no adverse events. During a period of 24 months, 27 MACE (14.7%) occurred in patients and controls with no statistical difference between groups. During a median follow-up of 33.7 months (IQR 37.6 months), 6 deaths (6.3%) occurred. Type of stress agent, thrombus mobility, or protrusion were not correlated to embolic events or death. Conclusion: The addition of a stress test to a CMR exam is safe and does increase the generally high cardioembolic event rate in LV thrombus patients. Therefore, it is useful to support reperfusion decision-making.